Efficacy and Safety of Anti-TNF Biosimilars for Psoriasis in Pediatric and Geriatric Populations: A 72-Week Real-Life Study - Megna M; Fornaro L; Potestio L; Luciano MA; Nocerino M; Delfino M; Guarino M; Fabbrocini G; Camela E (Dove Medical Press, 2022)
Matteo Megna, Luigi Fornaro, Luca Potestio, Maria Antonietta Luciano, Mariateresa Nocerino, Mario Delfino, Maria Guarino, Gabriella Fabbrocini, Elisa Camela Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Naples, NA, ItalyCorrespondence: Elisa Camela, Section of Dermatology - Department of Clinical Medicine and Surgery, University of Naples Federico II, Via Pansini 5, Naples, NA, 80131, Italy, Tel +39 - 081 - 7462457, Fax +39 - 081 - 7462442, Email elisacamela@gmail.comPurpose: To determine the efficacy and safety of adalimumab (ADA) and etanercept (ETA) biosimilars in elderly and children with psoriasis.Methods: A real-life retrospective observational study was conducted on pediatric (< 18 years) and geriatric (≥ 65 years) psoriasis patients treated with anti-TNF biosimilar agents referring to the Psoriasis Unit of the University of Naples Federico II, Italy, from January 2018 to January 2022. At baseline, demographic characteristics (age and sex), data on psoriasis duration and severity (measured by Psoriasis Area Severity Index [PASI] and body surface area [BSA]), presence of psoriatic arthritis if applicable, comorbidities, and previous psoriasis treatments were recorded. Patients were monitored by regular follow-ups (week 12, 24, 48 and 72) through clinical and haematological assessments and adverse events (AEs) were registered.Results: A total of 11 children and 23 elderly psoriasis patients were enrolled. Concerning children, 6 (54.5%) were under ADA biosimilar and 5 (45.5%) under ETA biosimilar. ETA and ADA biosimilars were equally effective and safe for up to 72 weeks (mean PASI and BSA < 3). No significant AEs were reported, and none discontinued treatment. In the elderly, 15 (65.2%) were treated with ADA biosimilar and 8 (34.8%) with ETA biosimilar. ETA and ADA biosimilars were equally effective up to 72 weeks (mean PASI < 4 and mean BSA < 5%). AEs (mainly mild) were registered in 9 subjects (39.1%). Also, 4 (17.4%) patients discontinued biologicals for secondary lack of efficacy (3, 75%) or AEs (1, 25%).Conclusion: Our study found that ADA and ETA biosimilars are effective and safe for the treatment of moderate-to-severe psoriasis in children and the elderly. No statistically significant efficacy and safety differences were found between ADA and ETA biosimilars in both children and the elderly. Geriatric patients displayed a higher discontinuation rate and side effects than the pediatric counterpart even if without approaching statistical significance.Keywords: psoriasis, etanercept, adalimumab, biosimilar, treatment